1996
DOI: 10.1073/pnas.93.1.284
|View full text |Cite
|
Sign up to set email alerts
|

Expression cloning and functional characterization of the kidney cortex high-affinity proton-coupled peptide transporter.

Abstract: The presence of a proton-coupled electrogenic high-affinity peptide transporter in the apical membrane of tubular cells has been demonstrated by microperfusion studies and by use of brush border membrane vesicles. The transporter mediates tubular uptake of filtered di-and tripeptides and aminocephalosporin antibiotics. We have used expression cloning in Xenopus laevis oocytes for identification and characterization of the renal high-affinity peptide transporter. Injection of poly(A)+ RNA isolated from rabbit k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
143
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(158 citation statements)
references
References 22 publications
14
143
0
Order By: Relevance
“…Novotny et al (2000) also reported that PEPT2 is one of the two transporters responsible for ALA incorporation at the choroid plexus. Results here presented indicate that in our murine mammary adenocarcinoma cell cultures ALA is not incorporated by any of these transporters since their substrates, the dipeptide gly-gly, the tripeptide gly-gly-ala and the angiotensinconverting enzyme inhibitor captopril (Boll et al, 1996) do not significantly block ALA uptake. Washed cells were preincubated for 15 min with 2 mM ouabaine or 0.1 mM dimethylamiloride or for 60 min with 100 mM 2-deoxy-D-glucose plus 10 mM Na 3 N. Then 0.1 mM 14 C-ALA or 0.1 mM 14 C-GABA was added and radioactivity was measured after 30 min.…”
Section: Discussionmentioning
confidence: 68%
“…Novotny et al (2000) also reported that PEPT2 is one of the two transporters responsible for ALA incorporation at the choroid plexus. Results here presented indicate that in our murine mammary adenocarcinoma cell cultures ALA is not incorporated by any of these transporters since their substrates, the dipeptide gly-gly, the tripeptide gly-gly-ala and the angiotensinconverting enzyme inhibitor captopril (Boll et al, 1996) do not significantly block ALA uptake. Washed cells were preincubated for 15 min with 2 mM ouabaine or 0.1 mM dimethylamiloride or for 60 min with 100 mM 2-deoxy-D-glucose plus 10 mM Na 3 N. Then 0.1 mM 14 C-ALA or 0.1 mM 14 C-GABA was added and radioactivity was measured after 30 min.…”
Section: Discussionmentioning
confidence: 68%
“…Surprisingly, the corresponding histidine residues are also conserved in the putative membrane-spanning c~-helices of PEPT2 from the human [19], rabbit [28] and rat [22] kidney. Miyamoto et al [30] also reported that essential histidine residues might be present at the dipeptide-binding site of the rabbit renal dipeptide transporter.…”
Section: Discussionmentioning
confidence: 99%
“…Recent molecular approaches have revealed that two structurally different H+-coupled peptide transporters are localized in the intestine and kidney: PEPT1 is expressed primarily in the small intestine and to a lesser extent in the kidney [16,17,21], whereas the PEPT2 is expressed specifically in the kidney [19,22,28]. These transporters exhibit about 50% amino acid identity.…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme assays rabbits, humans and rats [11][12][13][14][15][16], including a report from Alkaline phosphatase and Na+/K+-ATPase were assayed as deour laboratory [17]. The first report concerned rabbit intesscribed by Pekarthy et al [19] and Scharscbmidt et al [20], respectively.…”
mentioning
confidence: 99%